Online Payment Accounting Information System Credit On Cv. Yoga Solafide Finance - Sinta Astuti Simatupang (Jurnal Mekintek : Jurnal Mekanikal, Energi, Industri, Dan Teknologi, 2023)
Currently a computer application system is needed to facilitate work. With this application, we can manage the data we have to produce an information system that is definitely better and more useful for certain needs. But not infrequently there are several companies or agencies such as CV. Yoga Solafide Finance has not yet implemented this in its performance processes such as credit payments so that generating information takes quite a long time and sometimes errors occur due to the absence of a special system for managing credit payment data on CV. Yoga Solafide Finance. For this reason, it is necessary to create a system to manage credit payment data made using Microsoft Visual Basic 2010 and Microsoft SQL Server 2008 applications. It is hoped that this system can reduce system weaknesses in CV. Yoga Solafide Finance